Development of Mystery Box Learning Media to Improve Elementary School Students' Learning Outcomes - Shafa Alika Nuradhisti; Fitria Dwi Prasetyanigtyas (Jurnal Penelitian Pendidikan IPA, 2025)
This study uses the Research and Development (R&D) method with the Borg & Gall development model, which has been adjusted by Sugiyono into eight main stages: identification of potential and problems, data collection, product design, design validation, design revision, product trial, product refinement, and usage trial. The subjects of this study were 27 fourth-grade students of SDN Purwoyoso 01. Data collection was carried out through questionnaires, observations, interviews, and documentation, which were analyzed using product data analysis techniques, initial data analysis, and final data analysis. The results of the study showed that: Mystery Box media is very feasible to use, with a feasibility level of 88% from media experts and 82.66% from material experts; Mystery Box has been proven to improve student learning outcomes, with a t-test value of 10.677 and an average increase (gain) of 0.71; and This learning media is effective and feasible to be applied in science learning, especially in the material of Indonesian Cultural Diversity. For further research, it is recommended that the development of Mystery Box be carried out on other materials, with design refinement and additional references to deepen the learning content.